Connections between lower urinary tract symptoms related to benign prostatic enlargement and metabolic syndrome with its components: a systematic review and meta-analysis. (2nd October 2015) - Russo, Giorgio Ivan; Castelli, Tommaso; Urzì, Daniele; Privitera, Salvatore; Fragalà, Eugenia; La Vignera, Sandro; Condorelli, Rosita A.; Calogero, Aldo E.; Favilla, Vincenzo; Cimino, Sebastiano; Morgia, Giuseppe
Abstract: A significant amount of epidemiological evidences have underlined an emerging link between metabolic syndrome (MetS) and lower urinary tract symptoms (LUTS) secondary to benign prostatic enlargement a (BPE). We aimed to assess the connections between LUTS and MetS with its components. Meta-analysis were conducted to determine the mean differences (MD) and confidence intervals of IPSS total score, IPSS-voiding, IPSS-storage and prostate volume (PV) in patients with or without MetS. Ln(odds-ratio) were calculated to estimate the risk of having moderate-to-severe LUTS (IPSS ≥ 8). Nineteen studies were identified as eligible for this systematic review, with a total of 18, 476 participants, including 5554 (30.06%) with and 12 922 (69.94%) without MetS. Pooled analysis did not demonstrate significant MD of IPSS, IPSS-voiding and IPSS-storage in men with or without MetS but PV was significantly different (MD = 2.18; p  = 0.03). Presence of MetS was not significantly associated with moderate-to-severe LUTS (odds ratio = 1.13; p  = 0.53) and only altered serum triglycerides and diabetes were associated with this risk. The association between MetS and LUTS/BPE remain unclear and further observational studies in a population with metabolic disorders should be conducted in order to address it's potential role in determining LUTS/BPE.